Forest associations of the National Park Mavrovo in the Republic of Macedonia - Acevski, Jane; Simovski, Bojan (Editura Universitătii Ştefan cel Mare Suceava, 2012)
In this scientific paper are observed data related to research conducted of the phytocoenological characteristics of the territory of the National Park Mavrovo in the Republic of Macedonia. Therefore, visited and explored were the mountain massifs: Shar Planina, Korab and Bistra. Within the completed surveys, the standard phytocoenological method of Braun-Blanquet was used. On the teritory of the Park, authors noted and identified 28 forest communities (19% of the 148 identified plant communities in the Republic of Macedonia), i.e. 4 coastal floodplain (riparian) forest communities, 18 typical forest communities and 6 degraded-coppice forests. Coppice forests until now have not been guided in the literature. Also were disclosed forests with virgin forest’s character. In addition to natural forest communities, listed are artificial forest stands. Likewise, were discovered new data of certain phytocoenological phenomena, as in the Park, and in Macedonia. New insights arising from this research are particularly important, taking into account the rapid progress of studies on vegetation in Europe (creating ecological networks) and thus solve the important forest ecosystem problems. Extensive scientific work will undoubtedly lead to the creation of a solid and relevant base of phytocoenological data that will provide the conditions for protection of significant forest communities in the Park and thus in Macedonia.
Published scientific conference contribution
Keywords: forest association; forest community; forest ecosystem; National Park Mavrovo